SANGGAR TARI SEBAGAI PATNER DALAM PENDIDIKAN SEKOLAH KEJURUAN TARI - Sriyadi Sriyadi (Institut Seni Indonesia Surakarta, 2016)
The dance studio in societal life is very expected because young generation have less interested intradition arts especially dancing and local arts like karawitan. Our people very expect the dance studio and other similar studio in their life to give necessary skill in dancing, either to build field ofen deavor or enter work force. Method which used is lecture, drill, and creative. The dance studio results in more advantages for society.Key words : dance studio, Javanese tradition.